Flame retardant resin composition and article made therefrom

The existing resin compositions are solved at high frequencies and high frequencies by using 4-vinylbenzyldiphenylphosphine oxide and vinyl-terminated polyphenylene ether resins in the resin composition and using free radical polymerization and cocuring techniques. The problem of high dielectric loss and flammability at temperatures has achieved a resin composition with low dielectric loss and high heat resistance.

CN119487090APending Publication Date: 2025-02-18AISLE-AIBO AMERICA CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202380054233.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-21
Filing Date
2023-07-17
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing resin compositions have problems such as high dielectric loss, low glass transition temperature and flammability at high frequencies and high temperatures, making it difficult to meet the requirements of the new generation of electronic devices.

Method used

A composition comprising 4-vinylbenzyldiphenylphosphine oxide and vinyl terminated polyphenylene ether resin is used, and a resin combination with low dielectric loss and high heat resistance is formed by radical polymerization and co-curing techniques. Things.

Benefits of technology

The resin composition with low dielectric constant and low dissipation factor at 80 GHz is achieved while maintaining high thermal stability at temperatures above 370°C, meeting the application needs of electronic devices at high frequencies and high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119487090A_ABST
    Figure CN119487090A_ABST
Patent Text Reader

Abstract

Provided herein is a flame retardant, halogen-free resin composition comprising (a) a radically polymerizable monomer or oligomer; and (b) a 4-vinylbenzyldiphenylphosphine oxide of formula (I), and wherein the composition is free of maleimide resins. Also provided are articles that may be prepared from the composition, which may be prepregs, resin films, laminates, or printed circuit boards. The article has low dielectric loss at very high frequencies. # imgabs0 #
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to a resin composition, more particularly a flame retardant resin composition, which is used in the field of electronic devices and has low dielectric loss, high Tg and high heat resistance. Background Art

[0002] With the widespread popularity of 5G communication technology, electronic products are changing every day, requiring faster data transmission speeds and higher system operating frequencies. At the same time, lead-free soldering requires materials to withstand higher temperatures. To meet higher requirements, high-frequency, high-speed, low-loss, high-Tg copper clad laminates must meet the basic conditions for such applications.

[0003] Epoxy phenolic resin systems, which are conventionally used in copper clad laminates (CCLs), have high dielectric losses, which limits their use in the field of high frequency and high speed applications. Many resins developed to replace epoxy-based systems are more flammable than epoxies and require the use of very effective flame retardants to meet the requirements of electronic communication technology. Most of these flame retardants have a negative impact on electrical properties.

[0004] For example, polyphenylene oxide (PPO) resin is widely used to manufacture low dielectric copper clad laminates. However, copper clad laminates made of PPO resin alone have a low glass transition temperature (Tg), and PPO resin shows poor compatibility with other resins, which causes problems of high thermal expansion rate and poor heat resistance. As a result, polyphenylene oxide resin alone has been unable to meet the requirements of a new generation of high frequency and low dielectric circuit boards.

[0005] The object of the present invention is to provide a flame retardant which is compatible with PPO resins and provides a composition having a Df below 0.003 and a Dk below 2.8 at very high frequencies of 80 GHz while maintaining high thermal stability with an onset of decomposition above 370°C.

[0006] Bismaleimide has been introduced to attempt to provide lower thermal expansion and high heat resistance in resin systems. But this approach has led to a deterioration in the dielectric properties of the resin. Therefore, vinyl terminated PPO has been used to chemically bond to resins such as polybutadiene, SBR rubber or C5 aliphatic resins. This eliminates compatibility issues. Low Tg has been solved by using crosslinking agents such as triallyl isocyanurate.

[0007] The problem is that such a combination of resins is highly flammable. It is a difficult task to find a flame retardant that is compatible with such a cross-linked resin, which does not cause a deterioration in electrical properties or thermal stability. The additive flame retardant must have a very high melting point so as not to reduce Tg. It must also be easy to disperse in a varnish. In order to achieve good dispersibility of a high melting point additive flame retardant in a varnish, grinding is required. This operation is intended to reduce the particle size to less than a few microns. Such fine grinding requires specially designed expensive equipment and is accompanied by a loss of the ground product. On the other hand, reactive flame retardants can become incorporated into the resin, providing a uniform distribution so that dispersibility problems do not occur. However, it is an important challenge to find such compounds that do not have a negative impact on electrical properties, Tg and thermal stability. In addition, the compatibility of flame retardants with other varnish components is equally important.

[0008] Accordingly, there is a need to develop materials for copper clad laminates which overcome most of the aforementioned technical problems. Summary of the invention

[0009] The present invention herein belongs to the technical field of laminates, and relates to a thermosetting resin composition, a prepreg and a copper clad laminate using the thermosetting resin composition.

[0010] Provided herein are compositions comprising:

[0011] (a) free radical polymerizable monomers or oligomers; and,

[0012] (b) 4-vinylbenzyldiphenylphosphine oxide having the formula (I):

[0013] (I) And wherein the composition is free of maleimide resin.

[0014] Also provided herein is a process for making a laminate containing a composition described herein, the process comprising: impregnating the composition into a filler material to form a prepreg, then processing the prepreg at an elevated temperature to promote partial curing to the B-stage, and then laminating two or more of the prepregs at elevated pressure and temperature to form a laminate. The laminate has low dielectric losses at very high frequencies. DETAILED DESCRIPTION

[0015] The inventors herein have discovered that 4-vinylbenzyldiphenylphosphine oxide as shown in the structure of formula (I) above participates in a curing process together with a free radical polymerizable monomer or oligomer (a), most preferably a vinyl terminated PPO in an amount of at least 40 wt%. The curing process produces a composition with unexpectedly low Df at high frequencies such as 80 GHz. Since 4-vinylbenzyldiphenylphosphine oxide is incorporated into the vinyl terminated PPO resin during the curing process, it does not need to have a high melting point.

[0016] In the present invention, 4-vinylbenzyldiphenylphosphine oxide is added to the varnish and co-cured with the free radical polymerizable monomer or oligomer described herein. As a result, a resin composition is obtained, which is a composite material having low thermal expansion coefficient, high heat resistance, high glass transition temperature, low dielectric constant equal to or less than 2.72 at 80 GHz, and unexpectedly low dissipation factor of 0.0022 at 80 GHz.

[0017] It will be understood herein that all ranges herein include all subranges therebetween, and any combination of endpoints of the ranges.

[0018] Unless otherwise indicated, all weight percentages herein are based on the total weight of the reaction components.

[0019] Unless otherwise indicated, all temperatures herein are room temperature.

[0020] All viscosity measurements listed herein are at 25 degrees Celsius and are made using a Brookfield capillary viscometer. Unless otherwise indicated, all pressures indicated herein are 1 atmosphere at sea level and at 25 degrees Celsius.

[0021] The free radical polymerizable monomer or oligomer (a) described herein comprises one or more unsaturated bonds / molecule. Unless otherwise specified, the unsaturated bonds of the free radical polymerizable monomer or oligomer (a) are reactive unsaturated bonds, such as but not limited to double bonds with the potential for crosslinking with other functional groups, such as unsaturated carbon-carbon double bonds with the potential for crosslinking with other functional groups, but not limited thereto.

[0022] In one embodiment, the monomer or oligomer capable of free radical polymerization comprises a vinyl terminated polyphenylene ether resin. The vinyl terminated PPO resin is terminated by vinyl groups at both ends. Examples of vinyl terminated polyphenylene ether resins include, but are not limited to, vinyl benzyl terminated polyphenylene ether resins (e.g., available from Mitsubishi Gas Chemical Co., Inc.'s OPE-2st), methacrylate terminated polyphenylene ether resins (e.g., available from Sabic's SA9000), vinyl benzyl-modified bisphenol A polyphenylene ether resins, vinyl-containing chain-extended polyphenylene ether resins, or combinations thereof. For example, the vinyl terminated polyphenylene ether resin can be added to 4-vinylbenzyldiphenylphosphine oxide having formula (I) in any ratio as described above.

[0023] Most preferably, the free radical polymerizable monomer or oligomer (a) described herein may comprise vinyl terminated PPO in an amount of at least 40 wt%.

[0024] The free radical polymerizable monomer or oligomer (a) described herein may further include other components as described below, in addition to the vinyl terminated PPO in an amount of 40 wt%.

[0025] In one embodiment herein, the free radical polymerizable monomer or oligomer (a) may additionally be such that it contains a vinyl group or an allyl group, preferably an olefin or diene monomer or oligomer. More preferably, the free radical polymerizable monomer or oligomer is selected from a vinyl-containing compound, an allyl-containing compound, an acrylate resin, a polyolefin, and a combination thereof.

[0026] Even more preferably, the free radical polymerizable monomer or oligomer may be further selected from styrene, tert-butylstyrene, divinylbenzene, bis(vinylbenzyl)ether, bis(vinylphenyl)ethane, 1,2,4-trivinylcyclohexane, vinyl terminated polyphenylene ether resin, vinylbenzyl terminated polyphenylene ether resin, methacrylate terminated polyphenylene ether resin, vinylbenzyl modified bisphenol A polyphenylene ether resin, polybutadiene, isoprene, polyisoprene, piperylene, trans-1,3-pentadiene, cis-1,3-pentadiene, 2-methyl-2-butene, dicyclopentadiene, cyclopentadiene, cyclopentene, triallyl isocyanurate, triallyl cyanurate, diallyl bisphenol A, allyl modified tetramethyl bisphenol, allyl containing phenolic resin, allyl containing dicycloisoprene phenolic resin, methacrylic acid acrylate, octadecyl methacrylate, 2-phenoxyethyl methacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane di(meth)acrylate, 1,1-dodecanediol dimethacrylate, trimethylol-propane trimethacrylate, styrene-butadiene-divinylbenzene terpolymer, vinyl-polybutadiene-urethane oligomer, styrene-butadiene copolymer, hydrogenated styrene-butadiene copolymer, styrene-isoprene copolymer, polybutadiene, methyl styrene copolymer, styrene-ethylene copolymer, styrene-propylene copolymer, styrene-butadiene-isoprene terpolymer, hydrogenated styrene-butadiene terpolymer, hydrogenated styrene-isoprene copolymer, hydrogenated styrene-butadiene-isoprene terpolymer, and combinations thereof.

[0027] According to the present disclosure, the type of the free radical polymerizable monomer or oligomer resin is not particularly limited, provided that it contains 40 wt % of vinyl terminated PPO, and may include small molecule vinyl-containing compounds, allyl-containing compounds, acrylate resins, polyolefins, or combinations thereof.

[0028] In one embodiment, the monomer or oligomer capable of free radical polymerization comprises a small molecule vinyl-containing compound. As used herein, a small molecule vinyl-containing compound refers to a vinyl-containing compound having a molecular weight less than or equal to 1,000, preferably between 100 and 900, and more preferably between 100 and 800. According to the present disclosure, the small molecule vinyl-containing compound may include, but is not limited to, divinylbenzene (DVB), bis(vinylbenzyl) ether (BVBE), bis(vinylphenyl) ethane (BVPE), 1,2,4-trivinylcyclohexane (TVCH), or a combination thereof.

[0029] In one embodiment, the monomer or oligomer capable of free radical polymerization comprises an allyl-containing compound. The allyl-containing compound is a compound containing an allyl group and is not particularly limited, preferably an allyl-containing resin with two or more allyl groups / molecules. The allyl-containing resin may also contain other functional groups, such as epoxy groups, hydroxyl groups, etc. Examples of the allyl-containing compound include but are not limited to triallyl isocyanurate (TAIC), triallyl cyanurate (TAC), diallyl bisphenol A, allyl-modified tetramethyl bisphenol, allyl-containing phenolic resin, allyl-containing dicycloisoprene phenolic resin, or a combination thereof. Preferably, the allyl-containing compound comprises allyl-modified tetramethyl bisphenol, allyl-containing dicycloisoprene phenolic resin, or a combination thereof.

[0030] In one embodiment, the monomer or oligomer capable of free radical polymerization comprises an acrylate resin. The acrylate resin may comprise a monofunctional acrylate resin, a difunctional acrylate resin, or a trifunctional acrylate resin, but is not limited thereto. For example, the monofunctional acrylate resin may comprise, but is not limited to, dodecyl methacrylate, octadecyl methacrylate, 2-phenoxyethyl methacrylate, or a combination thereof. The difunctional acrylate resin may comprise, but is not limited to, tricyclodecane dimethanol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, 1,12-dodecanediol dimethacrylate, or a combination thereof. The trifunctional acrylate resin may comprise trimethylolpropane trimethacrylate.

[0031] For example, the monofunctional acrylate resin may be a monofunctional long chain alkyl acrylate sold by Sartomer under the trade names SR313A, SR313B, SR313NS, SR324NS, SR335, and SR489D. For example, the difunctional acrylate resin may be a difunctional acrylate sold by Sartomer under the trade names SR-833S, SR-238NS, SR-239, and SR-262. For example, the trifunctional acrylate resin may be a trifunctional acrylate sold by Sartomer under the trade name SR-350NS.

[0032] In one embodiment, the monomer or oligomer capable of free radical polymerization comprises a polyolefin. Examples of polyolefins include, but are not limited to, polymers containing one or more monomers selected from the following: ethylene, propylene, 1-butene, 1-pentene, 1-hexene, 4-methyl-1-pentene, 1-octene, 1-decene, etc., or random polypropylene, ethylene-ethyl acrylate copolymers, etc. Examples include: styrene-butadiene-divinylbenzene terpolymers, styrene-butadiene-maleic anhydride terpolymers, vinyl-polybutadiene-urethane oligomers, styrene-butadiene copolymers, styrene-isoprene copolymers, polybutadiene (homopolymer of butadiene), maleic anhydride-butadiene copolymers, methyl styrene copolymers, styrene-ethylene copolymers, styrene-propylene copolymers, styrene-butadiene-isoprene terpolymers, or combinations thereof.

[0033] The polyolefin preferably includes a polyolefin having an elongation percentage (elongation %) greater than or equal to 500%, such as but not limited to D-1117, D-1118, G-1652, G-1701, G-1702, G-1750, G-1765, G-1780, etc. In addition, the polyolefin preferably has an elongation percentage ranging from 500% to 1500%.

[0034] The free radical polymerizable monomer or oligomer (a) and the 4-vinylbenzyldiphenylphosphine oxide (b) of formula (I) may be present in any ratio. For example, the free radical polymerizable monomer or oligomer may be present in the composition in an amount of 40 to about 95 weight percent, preferably about 55 to about 90 weight percent, and most preferably about 65 to about 85 weight percent, and the 4-vinylbenzyldiphenylphosphine oxide of formula (I) may be present in an amount of 5 to about 60 weight percent, preferably about 10 to about 45 weight percent, and most preferably about 15 to about 35 weight percent.

[0035] In one embodiment, the composition according to the present disclosure may optionally further include: an epoxy resin, an amine curing agent, a phenol curing agent, an anhydride curing agent, a benzoxazine resin, a cyanate resin, or any combination thereof, but is not limited thereto.

[0036] Furthermore, the composition according to the present disclosure may optionally further include: an inorganic filler, a curing accelerator, a solvent, a silane coupling agent, a colorant, or a combination thereof.

[0037] In one embodiment of the present disclosure, the composition may optionally further include an inorganic filler, a curing accelerator, a solvent, a molecular weight regulator, a polymerization inhibitor, a toughening agent, a coupling agent, or a combination thereof. Unless otherwise specified, the content of the above components may be 1 to 200 parts by weight, such as 5, 10, 20, 30, 40, 50, 60, 70, 80, 90, 100, 150 or 200 parts by weight, relative to a total of 100 parts by weight of the free radical polymerizable monomer or oligomer; and additives.

[0038] For example, the composition of the present disclosure may additionally contain an inorganic filler to enhance the dimensional stability of the article manufactured by the resin composition. The inorganic filler may be any inorganic filler known in the art to which the present disclosure belongs, examples including but not limited to silicon dioxide (molten, non-molten, porous or hollow type), aluminum oxide, aluminum hydroxide, magnesium oxide, magnesium hydroxide, calcium carbonate, aluminum nitride, boron nitride, aluminum silicon carbide, silicon carbide, titanium dioxide, zinc oxide, zirconium oxide, mica, boehmite (AlOOH), calcined talc, talc, silicon nitride, calcined kaolin, or a combination thereof. In addition, the inorganic filler may be spherical, fibrous, plate-like, granular, flaky or whisker-like in shape, and may be optionally pretreated by a silane coupling agent.

[0039] For example, the composition of the present disclosure may additionally contain a curing accelerator to enhance the reactivity of the components in the composition. The curing accelerator (including a curing initiator) may be any curing accelerator known in the art to which the present disclosure belongs, and examples include, but are not limited to, catalysts such as Lewis bases, Lewis acids, or combinations thereof. The Lewis base may include any one or more of the following: imidazole, boron trifluoride-amine complex, ethyltriphenylphosphine chloride, 2-methylimidazole (2MI), 2-phenyl-1H-imidazole (2PZ), 2-ethyl-4-methylimidazole (2E4MI), triphenylphosphine (TPP) and 4-dimethylaminopyridine (DMAP). The Lewis acid may include metal salt compounds, such as those of manganese, iron, cobalt, nickel, copper and zinc, such as zinc octoate or cobalt octoate. The curing accelerator also includes a curing initiator, such as a peroxide capable of generating free radicals. The curing initiator may include dicumyl peroxide, tert-butyl perbenzoate, dibenzoyl peroxide, 2,5-dimethyl-2,5-di(tert-butylperoxy)-3-hexyne, bis(tert-butylperoxyisopropyl)benzene, or a combination thereof, but is not limited thereto.

[0040] For example, the composition of the present disclosure may further contain a solvent to adjust the viscosity of the varnish formed therefrom. The solvent may include, but is not limited to, methanol, ethanol, ethylene glycol monomethyl ether, acetone, butanone (methyl ethyl ketone), methyl isobutyl ketone, cyclohexanone, toluene, xylene, methoxyethyl acetate, ethoxyethyl acetate, propoxyethyl acetate, ethyl acetate, dimethylformamide, dimethylacetamide, propylene glycol methyl ether, or a mixture thereof.

[0041] For example, the composition of the present disclosure may further contain a silane coupling agent to facilitate the dispersion of the inorganic filler. The silane coupling agent may include a silane such as, but not limited to, siloxane, and may be further classified into aminosilanes, epoxysilanes, vinylsilanes, acrylatesilanes, methacrylatesilanes, hydroxysilanes, isocyanatesilanes, methacryloxysilanes, and acryloxysilanes according to the functional group.

[0042] The composition according to the present disclosure can be processed to manufacture various articles, including but not limited to prepregs, resin films, laminates or printed circuit boards. For example, the composition can be used to manufacture resin films as follows: the composition is coated on a carrier, and then heated and baked to semi-cured the composition. The carrier may include polyethylene terephthalate film (PET film), polyimide film (PI film), copper foil or resin-coated copper (RCC). For example, the composition can be selectively coated on polyethylene terephthalate film (PET film), polyimide film (PI film), copper foil or resin-coated copper (RCC), then heated and baked to semi-cured the composition to form a resin film.

[0043] For example, the composition can be used to manufacture a laminate comprising two metal foils and an insulating layer arranged between the metal foils, wherein the insulating layer is manufactured by curing a phosphorus-containing resin composition to a C-stage at high temperature and high pressure, and a suitable curing temperature is, for example, between 150°C and 220°C, and preferably between 190°C and 210°C, and a suitable curing time is 90 to 180 minutes, and preferably 90 to 150 minutes. The insulating layer can be obtained by curing the aforementioned prepreg or resin film. The metal foil may include copper, aluminum, nickel, platinum, silver, gold, or an alloy thereof, such as copper foil. For example, the laminate may be a copper clad laminate (CCL).

[0044] Furthermore, the laminate may be further processed by a trace formation process to provide a printed circuit board (aka circuit board).

[0045] Generally, compositions according to the present disclosure or articles made therefrom can achieve one or more of the following features:

[0046] Articles made from the compositions disclosed herein may have at least one, preferably at least two, more or all of the following properties:

[0047] When measured by using a dynamic mechanical analyzer in accordance with IPC-TM-650 2.4.24.4, a glass transition temperature of greater than or equal to 216°C, such as between 216°C and 240°C or between 220°C and 230°C; when measured by using a thermal mechanical analyzer in accordance with IPC-TM-650 2.4.24.5, a thermal expansion coefficient in the Z axis of less than or equal to 2.70%, such as between 2.20% and 2.70%; when measured by using a tensile strength tester in accordance with IPC-TM-650 2.4.8, a copper foil peel strength of greater than or equal to 3.0 lb / inch, such as between 3.0 lb / inch and 3.8 lb / inch; when measured in accordance with IPC-TM-650 2.6.16.1, no delamination occurs after 5 hours of moisture absorption and then undergoes a solder dip test in accordance with IPC-TM-650 2.4.23; when measured in accordance with JIS a dissipation factor of less than or equal to 0.0030 at 80 GHz when measured with reference to JIS C2565; a dielectric constant of less than or equal to 3.10, such as between 2.50 and 3.10, or between 3.05 and 3.10, when measured with reference to JIS C2565; good sticking resistance (no sticking between prepregs) when measured as follows: a plurality of prepregs vacuum-packed in aluminum foil bags are stored at a constant temperature of 35° C. for 48 hours, and then visually inspected to determine the stickiness of the prepregs; and a shelf life of greater than or equal to 1 day (no precipitation, turbidity or layer separation after 1 day), such as greater than or equal to 2, 3, 5, 7, 9, 11 or 15 days, of a varnish made from the resin composition when measured as follows: a varnish made from the resin composition is standing still at 5-35° C., and visually inspected for precipitation, turbidity or layer separation.

[0048] Most preferably, the composition comprises 40-80 parts by weight of vinyl terminated PPO; and 10-50 parts by weight of polybutadiene; and 1-15 parts by weight of triallyl isocyanurate, wherein the flame retardant is 4-vinylbenzyldiphenylphosphine oxide, wherein the PPO resin is SA9000 from Sabic, and the polybutadiene is a liquid resin having a number average of less than 5000, and a minimum vinyl content of 20%, and a viscosity of less than 2000 poise at 45°C, and a Li ion content of less than 100 ppm.

[0049] Example

[0050]

[0051] Examples of performance are listed in Table 1 of the attached document.

[0052] The formulation components were mixed in the ratios listed in Table 1, B-staged at 150°C for 3 minutes, ground and cured at 175°C for 2 h, and then at 190°C for 1 h.

[0053] Table 1 Comparison of formulations and thermal properties of Inventive Example 1 and Comparative Examples 1-3.

[0054]

[0055] SA9000 (ex Sabic) Modified PPO with vinyl end groups

[0056] B1000 (ex NIPPON SODA) Homopolymer of butadiene

[0057] TAIC (ex Aldrich) 1,3,5-Triallyl-1,3,5-triazine-2,4,6(1H,3H,5H)-trione

[0058] Dicumyl peroxide (ex Aldrich)

[0059] Sample preparation: A sample of FR compound was combined with PPE resin SA9000 and crosslinker B-1000 and TAIC and cured on a small scale. The composition of the small scale sample is shown in Table 1 above. The total %P was about 2.4%. Toluene was used as solvent. The sample was cured at 175°C for 2 hours and post-cured at 190°C for 1 hour. The thermal stability of the sample was studied using DSC and TGA.

[0060] Table 2

[0061]

[0062] Surprisingly, as seen above, it was difficult to prepare a uniform film using the compounds from Comparative Examples 1 and 2, however, preparing a film using the compound from Example 1 was easy and formed a very uniform film.

[0063] Table 3

[0064]

[0065] *Quality not good enough for testing.

[0066] FR: flame retardant

[0067] 10GHz: AET microwave dielectric meter.

[0068] 80GHz: Keycom MDM-03, FPR-50.

[0069]

[0070] Example 1 - prepared according to EP 0147724

[0071]

[0072] Comparative Example 1 - Prepared according to US 3035096

[0073]

[0074] Comparative Example 2 - Prepared according to US 3975447

[0075] Although the present invention has been described with reference to specific modes, materials and embodiments, from the foregoing description, those skilled in the art can easily ascertain the essential characteristics of the invention, and can make various changes and modifications to adapt to different uses and features without departing from the spirit and scope of the invention as described above.

Claims

1. A composition comprising: (a) free radical polymerizable monomers or oligomers; and, (b) 4-vinylbenzyldiphenylphosphine oxide having the formula (I): (I), And wherein the composition is free of maleimide resin.

2. The composition of claim 1, wherein the free radical polymerizable monomer or oligomer contains a vinyl or allyl group.

3. The composition of claim 1, wherein the free radical polymerizable monomer or oligomer is an olefin or diene monomer or oligomer.

4. The composition of claim 1, wherein the free radical polymerizable monomer or oligomer comprises at least 40 weight percent vinyl terminated PPO.

5. The composition of claim 4, wherein the free radical polymerizable monomer or oligomer further comprises an additional component selected from the group consisting of vinyl-containing compounds, allyl-containing compounds, acrylate resins, polyolefins, and combinations thereof.

6. The composition according to claim 4, wherein the free radical polymerizable monomer or oligomer further comprises an additional component selected from the group consisting of styrene, tert-butylstyrene, divinylbenzene, bis(vinylbenzyl)ether, bis(vinylphenyl)ethane, 1,2,4-trivinylcyclohexane, polybutadiene, isoprene, polyisoprene, piperylene, trans-1,3-pentadiene, cis-1,3-pentadiene, 2-methyl-2-butene, dicyclopentadiene, cyclopentadiene, cyclopentene, triallyl isocyanurate, triallyl cyanurate, diallyl bisphenol A, allyl-modified tetramethyl bisphenol, allyl-containing phenolic resin, allyl-containing dicycloisoprene phenolic resin, dodecyl methacrylate, octadecyl methacrylate, 2-phenoxyethyl methacrylate, tricyclodecane dimethanol diacrylate, tricyclodecane di(meth)acrylate, 1,1-dodecanediol dimethacrylate, trimethylol-propane trimethacrylate, styrene-butadiene-divinylbenzene terpolymer, vinyl-polybutadiene-urethane oligomer, styrene-butadiene copolymer, hydrogenated styrene-butadiene copolymer, styrene-isoprene copolymer, polybutadiene, methyl styrene copolymer, styrene-ethylene copolymer, styrene-propylene copolymer, styrene-butadiene-isoprene terpolymer, hydrogenated styrene-butadiene terpolymer, hydrogenated styrene-isoprene copolymer, hydrogenated styrene-butadiene-isoprene terpolymer, and combinations thereof.

7. The composition according to claim 1, further comprising at least one of a flame retardant, an inorganic filler, a curing accelerator, a solvent, a molecular weight regulator, a polymerization inhibitor, a toughening agent, a coupling agent, or a combination thereof.

8. The cured composition of claim 1.

9. Any of a coating formulation, an encapsulant, a composite, an adhesive, a molded article, an adhesive sheet, or a laminated sheet comprising the composition according to claim 1.

10. An article comprising the composition according to claim 1.

11. The article of claim 10, wherein the article is useful in lead-free soldering applications and electronic devices.

12. The article of claim 10, wherein the article further comprises copper foil.

13. The article of claim 10, wherein the article is a printed circuit board.

14. A prepreg comprising the composition according to claim 1.

15. The prepreg according to claim 14, having a dielectric loss lower than or equal to 0.0030 0025 at 80 GHz, a glass transition temperature not lower than 180°C, and a thermal stability expressed as 5% weight loss in TGA not lower than 370°C.

16. A laminate or an adhesive sheet comprising the composition according to claim 1.

17. A printed wiring board comprising the prepreg according to claim 14.

18. A printed wiring board comprising the prepreg according to claim 14, having a dielectric loss lower than or equal to 0.0025 at 80 GHz, a glass transition temperature not lower than 180°C, and a thermal stability expressed as 5% weight loss in TGA of not lower than 370°C.

19. A printed wiring board comprising the laminate according to claim 16.

20. A process for making a laminate containing the composition according to claim 1, the process comprising: The composition is impregnated into a filler material to form a prepreg, which is then processed at an elevated temperature to promote partial cure to the B-stage, and two or more of the prepregs are then laminated at elevated pressure and temperature to form a laminate.

Citation Information

Patent Citations

  • Flame resistant alkenyl aromatic compounds and polymers containing chemically bonded phosphorus and blends with polyphenylene ether

    EP0147724A2

  • Indole-containing peptide and process for preparing the same

    EP0690070A1

  • Vinyl diphenylphosphine oxide and method of producing same

    US3035096A

  • Preparation of aromatic phosphine oxides by reaction of diarylhalophosphine and benzylic halide

    US3975447A